Legal Certainty in the Application of the Crime of Narcotics Abuse Judging from the Disparity of Judges' Decisions - Suhendar Suhendar; Annissa Rezki; Nur Rohim Yunus (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
Efforts to eradicate drug crimes present a law that has criminal sanctions, namely Law Number 35 of 2009 concerning Narcotics (abbreviated as the Narcotics Law) that criminal sanctions in the Narcotics Law are one of them with a death penalty. The Narcotics Law regulates the policy of criminal sanctions for drug abusers which are divided into two categories, namely the perpetrators as “Users” and/or “Dealers”. It is possible for perpetrators as dealers to be subject to the most severe criminal sanctions in the form of capital punishment as regulated in Article 114 paragraph (2). The method of legal discovery (rechtsvinding) that is often used by judges is the method of interpretation or interpretation. The results of the study state that the interpretation of the provisions that have been stated expressly must not deviate from the intent of the legislators. The judge has the authority to interpret the law if the content of the article used is unclear or incomplete. Analytical interpretation in the field of criminal law is prohibited insofar as it makes a formulation of the offense to be expanded. Analogous interpretation is permitted if it is used to fill the voids contained in the law because it has not been regulated in the provisions of the law.Keywords: Disparity; Judge; Drugs AbstrakUpaya untuk memberantas kejahatan narkoba menghadirkan sebuah Undang-Undang yang memiliki sanksi pidana yaitu Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika (disingkat UU Narkotika) bahwa Sanksi Pidana dalam Undang-Undang Narkotika salah satunya adalah sanksi pidana mati. Undang-Undang Narkotika mengatur mengenai kebijakan sanksi pidana bagi pelaku penyalahguna narkoba yang dibagi kedalam dua kategori yaitu pelaku sebagai “Pengguna” dan/atau “Pengedar”. Terhadap pelaku sebagai pengedar dimungkinkan dikenakan sanksi pidana yang paling berat berupa pidana mati seperti yang diatur dalam Pasal 114 ayat (2). Metode penemuan hukum (rechtsvinding) yang sering digunakan hakim yaitu metode interpretasi atau penafsiran. Hasil penelitian menyatakan bahwa Penafsiran terhadap ketentuan yang telah dinyatakan dengan tegas tidaklah boleh menyimpang dari maksud pembentuk Undang-Undang. Hakim mempunyai kewenangan untuk melakukan penafsiran hukum apabila isi pasal yang digunakan tidak jelas atau kurang lengkap. Penafsiran secara analogis di dalam lapangan hukum pidana terlarang sejauh ia membuat suatu rumusan delik itu menjadi diperluas. Penafsiran secara analogi diizinkan apabila digunakan untuk mengisi kekosongan-kekosongan yang terdapat di dalam Undang-Undang karena belum diatur dalam ketentuan Undang-Undang tersebut.Kata Kunci: Disparitas; Hakim; Narkoba